Recycling Study Guide - Hallowell, Anne.; Wisconsin State Dept. of Natural Resources, Madison ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
This study guide was designed to help teachers and students understand the problems surrounding solid wastes. It includes an overview of solid waste and recycling, a glossary, suggested activities and a list of resource publications, audiovisual materials and organizations. There are 19 activity suggestions included in this guide designed for use in grades 4 through 12. Topics include solid waste production, natural resources, landfills, composting, packaging, and decision making. Each activity includes goals, grade levels, materials, procedures, and discussion questions. In addition, 32 activity ideas are suggested. References are divided into general, composting and decomposition, curriculum materials, audiovisual materials, agencies, and organizations. Interdisciplinary cooperation is stressed throughout. (CW)
ERIC Note: Colored drawings may not reproduce well.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Conservation (Environment); Elementary School Science; Elementary Secondary Education; Environmental Education; Junior High Schools; Laboratory Procedures; Middle Schools; Recycling; Science Activities; Science Education; Secondary School Science; Solid Wastes; Teaching Methods; Waste Disposal; Composting; Guides, Classroom -- Teacher